Cardiac Arrest in Patients with Poor-Grade Aneurysmal Subarachnoid Hemorrhage: A Single-Center Experience - Ridwan, Sami; Kristof, Rudolf (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2019)
Background Poor-grade aneurysmal subarachnoid hemorrhage (SAH), in particular Hunt and Hess (H&H) grade 5 SAH, still has a high case-fatality rate. Recent studies regarding the clinical outcome of such patients and the influence of comorbidities, especially cardiac arrest (CA) requiring additional cardiopulmonary resuscitation (CPR), on the outcome of these patients are scant. Our primary objective was to assess the outcome of SAH H&H grade 5 patients and the influence of additional CA and requirement for CPR.Methods All patients with spontaneous aneurysmal SAH H&H grade 5 admitted to our hospital from 2001 to 2010 were enrolled in the study. Data were extracted from the hospital's clinical records and electronic database. The patients' clinical outcome at time of discharge was represented by the Glasgow Outcome Score and modified Rankin Scale (mRS). The influence of CA and additional CPR on patient outcome was analyzed.Results Of 80 SAH H&H grade 5 patients (median age 55 years), 21 patients (median age 50 years) experienced CA and received additional CPR. Mortality in SAH H&H grade 5 patients was 85% with CA and 68% without CA (p = 0.158). Overall, 22 of 59 patients with no CA survived, 4 with a good clinical outcome (mRS 0–3). Of the 21 with CA, only 3 survived, none with a good outcome (mRS 4–5). Due to the small subgroup surviving additional CA, a statistical difference could not be found between the groups. Aneurysm occlusion (p < 0.001) and aneurysm of the posterior circulation (p = 0.010) resulted in a more favorable clinical outcome.Conclusions Patients with SAH H&H grade 5 do survive and in 5% of cases even with a good outcome. Surviving an additional CA resulted in a less favorable outcome without statistical significance. Thus SAH H&H grade 5 patients with or without CA and additional CPR should not be excluded from appropriate neurosurgical treatment.
Keywords: vascular; aneurysm; subarachnoid hemorrhage; cardiac arrest